Relationship between Psychological Capital and Psychological Well-Being of Direct Support Staff of Specialist Autism Services. The Mediator Role of Burnout - Manzano-García, Guadalupe; Ayala, Juan-Carlos (Frontiers in Psychology, 2017)
This study investigates the specific role of burnout as a mediator in the relationship between psychological capital and psychological well-being in direct support staff of specialist autism services. A time lagged design with three data-collection points was conducted to survey 56 professionals (direct support staff) who work at a Spanish center specialized in autism. Participants completed measures of psychological capital, burnout and psychological well-being. The hypothesized model was tested using structural equation modelling. Our findings show that psychological capital has a significant main effect on psychological well-being. The results also show that psychological capital in the work environment should result in lower burnout which in turn, should lead to higher degrees of psychological well-being in the direct support staff of autism services. Our results support that psychological capital is a key variable in the working life of the direct support staff of autism services. The findings suggest the need of implementing programmes which strengthen each individual's psychological capital in order to prevent burnout and achieve a greater psychological well-being.